Analisis Filantropi Islam dan Etika Bisnis dalam Meningkatkan Kesejahteraan Masyarakat - Zian Nafisya; Ahmad Asas Hakiki; Sekar Triantis; Rizki Febriani (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. This study analyzes the role of Islamic philanthropy and business ethics in improving community welfare through a case study of Lazismu Pasuruan Regency. Pasuruan Regency continues to face poverty and economic vulnerability, highlighting the need for sustainable empowerment strategies. Lazismu distributes zakat, infaq, sadaqah, and waqf funds through economic empowerment, education, healthcare, and strategic partnerships with BPKH and the BankZiska program. This study employed a qualitative approach with a holistic single-case study design. Data were collected through interviews, observations, and documentation and analyzed using thematic analysis. The findings indicate that Islamic philanthropy has significant potential to enhance community welfare through business capital assistance, microenterprise development, and the empowerment of local livestock farmers. However, its implementation faces several challenges, including deviations from the Memorandum of Understanding (MoU), low beneficiary responsibility, revolving fund repayment defaults, and limited financial literacy. The success of Islamic philanthropy depends on the internalization of Islamic business ethics, including trustworthiness, honesty, responsibility, and professionalism, supported by effective supervision, spiritual mentoring, and business ethics education to achieve sustainable economic independence for mustahik. Abstrak. Penelitian ini menganalisis peran filantropi Islam dan etika bisnis dalam meningkatkan kesejahteraan masyarakat melalui studi kasus di Lazismu Kabupaten Pasuruan. Kabupaten Pasuruan masih menghadapi kemiskinan dan kerentanan ekonomi sehingga diperlukan strategi pemberdayaan yang berkelanjutan. Lazismu menyalurkan dana zakat, infak, sedekah, dan wakaf melalui program pemberdayaan ekonomi, pendidikan, kesehatan, serta kerja sama dengan BPKH dan program BankZiska. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus tunggal holistik melalui wawancara, observasi, dan dokumentasi yang dianalisis secara tematik. Hasil penelitian menunjukkan bahwa filantropi Islam berpotensi meningkatkan kesejahteraan masyarakat melalui bantuan modal usaha, penguatan usaha mikro, dan pemberdayaan peternak lokal. Namun, implementasinya masih menghadapi hambatan berupa penyimpangan pelaksanaan MoU, rendahnya tanggung jawab penerima manfaat, kemacetan pengembalian dana bergulir, dan lemahnya literasi keuangan. Keberhasilan filantropi Islam bergantung pada internalisasi nilai amanah, kejujuran, tanggung jawab, dan profesionalisme, didukung pengawasan, pendampingan spiritual, serta edukasi etika bisnis untuk mewujudkan kemandirian ekonomi mustahik yang berkelanjutan.